Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A Prospective Cohort Study of the Impact of Maternal Avocado Consumption During Pregnancy on Offspring Allergic Diseases: The Kuopio Birth Cohort Study (KuBiCo) - F. Cheng; S. Hantunen; L. Keski-Nisula; K. Backman; N. Ford (Journal of the Academy of Nutrition and Dietetics, 2024)

Coral bleaching response index: a new tool to standardize and compare susceptibility to thermal bleaching - Timothy D. Swain; Jesse B. Vega‐Perkins; William K. Oestreich; Conrad Triebold; Emily DuBois; Jillian Henss; Andrew Baird; Margaret Siple; Vadim Backman; Luisa Marcelino (Global Change Biology, 2016)
As coral bleaching events become more frequent and intense, our ability to predict and mitigate future events depends upon our capacity to interpret patterns within previous episodes. Responses to thermal stress vary among coral species; however the diversity of coral assemblages, environmental conditions, assessment protocols, and severity criteria applied in the global effort to document bleaching patterns creates challenges for the development of a systemic metric of taxon‐specific response. Here, we describe and validate a novel framework to standardize bleaching response records and estimate their measurement uncertainties. Taxon‐specific bleaching and mortality records (2036) of 374 coral taxa (during 1982–2006) at 316 sites were standardized to average percent tissue area affected and a taxon‐specific bleaching response index (taxon‐ BRI ) was calculated by averaging taxon‐specific response over all sites where a taxon was present. Differential bleaching among corals was widely variable (mean taxon‐ BRI = 25.06 ± 18.44%, ±SE). Coral response may differ because holobionts are biologically different (intrinsic factors), they were exposed to different environmental conditions (extrinsic factors), or inconsistencies in reporting (measurement uncertainty). We found that both extrinsic and intrinsic factors have comparable influence within a given site and event (60% and 40% of bleaching response variance of all records explained, respectively). However, when responses of individual taxa are averaged across sites to obtain taxon‐ BRI , differential response was primarily driven by intrinsic differences among taxa (65% of taxon‐ BRI variance explained), not conditions across sites (6% explained), nor measurement uncertainty (29% explained). Thus, taxon‐ BRI is a robust metric of intrinsic susceptibility of coral taxa. Taxon‐ BRI provides a broadly applicable framework for standardization and error estimation for disparate historical records and collection of novel data, allowing for unprecedented accuracy in parameterization of mechanistic and predictive models and conservation plans.

Itraconazole, gemfibrozil and their combination markedly raise the plasma concentrations of loperamide - Mikko Niemi; Aleksi Tornio; Marja K. Pasanen; Hanna Fredrikson; Pertti J. Neuvonen; Janne T. Backman (European Journal of Clinical Pharmacology, 2006)

Frequencies of single nucleotide polymorphisms and haplotypes of organic anion transporting polypeptide 1B1 SLCO1B1 gene in a Finnish population - Marja K. Pasanen; Janne T. Backman; Pertti J. Neuvonen; Mikko Niemi (European Journal of Clinical Pharmacology, 2006)

Integration of soil solarization with chemical, biological and cultural control for the management of soilborne diseases of vegetables - C. Stevens; V. A. Khan; R. Rodriguez-Kabana; L. D. Ploper; P. A. Backman; D. J. Collins; J. E. Brown; M. A. Wilson; E. C. K. Igwegbe (Plant and Soil, 2003)

Effect of methylprednisolone on CYP3A4-mediated drug metabolism in vivo - Villikka K.; Varis T.; Backman J.; Neuvonen P.; Kivistö K. (European Journal of Clinical Pharmacology, 2001)

Effect of grapefruit juice dose on grapefruit juice-triazolam interaction: repeated consumption prolongs triazolam half-life - J. J. Lilja; K. T. Kivistö; J. T. Backman; P. J. Neuvonen (European Journal of Clinical Pharmacology, 2000)

Effect of fluconazole on plasma fluvastatin and pravastatin concentrations - T. Kantola; J. T. Backman; M. Niemi; K. T. Kivistö; P. J. Neuvonen (European Journal of Clinical Pharmacology, 2000)

The area under the plasma concentration-time curve for oral midazolam is 400-fold larger during treatment with itraconazole than with rifampicin - J. T. Backman; K. T. Kivistö; K. T. Olkkola; P. J. Neuvonen (European Journal of Clinical Pharmacology, 1998)